Energy Storage: A Lyotropic Liquid‐Crystal‐Based Assembly Avenue toward Highly Oriented Vanadium Pentoxide/Graphene Films for Flexible Energy Storage (Adv. Funct. Mater. 12/2017). (March 2017) - Liu, Haiqing; Tang, Yanping; Wang, Chi; Xu, Zhixiao; Yang, Chongqing; Huang, Tao; Zhang, Fan; Wu, Dongqing; Feng, Xinliang
Abstract : In article number 1606269, Haiqing Liu, Dongqing Wu, Xinliang Feng, and co‐workers develop a lyotropic liquid crystal based assembly strategy to fabricate composite films of vanadium pentoxide nanobelts and graphene oxide sheets. The obtained composite films possess highly oriented layered structures, high electrical conductivity, good mechanical stability, and excellent flexibility, which allows their application as high performance electrodes in flexible energy storage devices.